2019
DOI: 10.1017/s0950268819001456
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of infection withHelicobacter pyloripositive and negative cytotoxin-associated gene A phenotypes among Arab and Jewish residents of Jerusalem

Abstract: We examined the prevalence and correlates of Helicobacter pylori (H. pylori) infection according to cytotoxin-associated gene A (CagA) phenotype, a main virulence antigen, among the ethnically diverse population groups of Jerusalem. A cross-sectional study was undertaken in Arab (N = 959) and Jewish (N = 692) adults, randomly selected from Israel's national population registry in age-sex and population strata. Sera were tested for H. pylori immunoglobulin G (IgG) antibodies. Positive samples were tested for vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The prevalence of H. pylori infection in our study was 35% (42% CagA positive). This concurs with our previous findings in the Israeli population 23,31 . As expected, children with H. pylori positivity had higher serum PGI and PGII levels and a lower PGI:PGII ratio than did children with H. pylori negativity 15 .…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of H. pylori infection in our study was 35% (42% CagA positive). This concurs with our previous findings in the Israeli population 23,31 . As expected, children with H. pylori positivity had higher serum PGI and PGII levels and a lower PGI:PGII ratio than did children with H. pylori negativity 15 .…”
Section: Discussionsupporting
confidence: 92%
“…H. pylori IgG antibody sero-prevalence was 83.3% (95% confidence interval (CI) 80.0-85.5%) and 61.4% (95% CI 57.7-65.0%) among Arabs and Jews, respectively. Among H. pylori positives, the respective cagA IgG antibody sero-positivity was 42.3% (95% CI 38.9-45.8%) and 32.5% (95% CI 28.2-37.1%) [44].…”
Section: Prevalence Of H Pylori Genotypes and Their Correlation Withmentioning
confidence: 97%
“…Interestingly, Muhsen et al [ 14 ], who also investigated H. pylori isolates in Arab and Jewish populations, demonstrated higher Cag A IgG antibodies in the Arab population. Another study, performed in Israeli children and adolescents, found higher H. pylori seroprevalence among Arab participants as compared to Jewish participants[ 15 ].…”
Section: Discussionmentioning
confidence: 99%